Hubungan Tingkat Pengetahuan pada Pasien Diabetes Melitus dengan Perilaku Pencegahan Katarak - Fitriyani, Selvia; Juliani, Enni; Sabarina Panjaitan , Ribka (Jurnal Pustaka Keperawatan (Pusat Akses kajian Keperawatan), 2025)
Diabetes mellitus is a chronic disease commonly found in the community and is often referred to as a “silent killer” because it frequently shows no symptoms in its early stages. Nevertheless, diabetes can lead to various serious complications, including eye disorders such as cataracts. Cataracts are a common ocular complication in individuals with diabetes and can potentially lead to permanent blindness if not treated promptly.Efforts to prevent complications from diabetes largely depend on the patient’s understanding of how to manage the disease. This includes controlling blood sugar levels, blood pressure, cholesterol, adopting a healthy lifestyle, adherence to medication, and undergoing regular eye examinations. A good level of knowledge helps shape a positive mindset, which in turn influences preventive behavior, including the prevention of cataracts. In other words, the higher a person’s knowledge about their disease, the better their preventive behavior tends to be.This study aims to determine the relationship between the level of knowledge among diabetes mellitus patients and their behavior in preventing cataracts at Hospital X, Jakarta. The study employs a quantitative approach with a cross-sectional design and involves 105 respondents who were selected through the distribution of questionnaires. Data analysis was conducted using the Spearman test and showed a significance value of 0.345 (p < 0.01). This result indicates a relationship between the level of knowledge and cataract prevention behavior, although with a weak correlation. These findings suggest that increasing patients’ knowledge still plays a role in shaping better preventive behavior